Global Patterns in Marine Sediment Carbon Stocks - Atwood, Trisha B.; Witt, Andrew; Mayorga, Juan; Hammill, Edd; Sala, Enric (Frontiers in Marine Science, 2020)
To develop more accurate global carbon (C) budgets and to better inform management of human activities in the ocean, we need high-resolution estimates of marine C stocks. Here we quantify global marine sedimentary C stocks at a 1-km resolution, and find that marine sediments store ~ 3117 (3006-3209) Pg C in the top 1 meter (more than twice that of terrestrial soils). Sediments in abyss/basin zones account for 75% of the global marine sediment C stock, and 52% of that stock is within the 200-mile Exclusive Economic Zones of countries. Currently, only ~2% of sediment C stocks are located in highly to fully protected areas that prevent the disturbance of the seafloor. Our results show that marine sediments represent a large and globally important C sink. However, the lack of protection for marine C stocks makes them highly vulnerable to human disturbances that can lead to their remineralization to CO2, further aggravating climate change impacts.